Awareness on Child Abuse among Students in Public Schools of Rural Municipality of Nepal - Chand, Nisha; Panta, Ganga; Ranjitkar, Uma Devi (Journal of Nursing Education of Nepal, 2024)
Introduction: Child abuse is a global issue, all around the world which violates the rights of the children affecting their personal, social and psychological development leaving a lifetime psychological scar. It can happen at home, in organizations, schools or communities by parents, caregivers, neighbors and teachers. School children’s self-awareness is very important to prevent child abuse. The study aimed to find out level of awareness of child abuse among students in public schools in the Rural Municipality of Nepal. Methods: A descriptive cross-sectional study was conducted among 250 students in grade 8, 9 and 10, selected through cluster sampling, using a self-administered questionnaire. Data were analyzed, using descriptive and inferential statistics such as frequency, percentage, mean, standard deviation, chi-square and fisher exact test. Results: The study found out that around half (46.8%) of the respondents had an average level and 28% had an inadequate level of awareness on child abuse with a mean score of 62.3 ±19.8. Majority (63.2%) of the respondents considered smoking and drinking alcohol as possible consequences of child abuse, 69.6% stated that sharing problems with parents or close friends is preventive measures and 82.0% were aware of reporting to the police administration if they experience abuse. A significant association was found between the level of awareness and educational level (p-value 0.000). Conclusion: The students have an average level of awareness about child abuse but significant number of students still lack adequate level of awareness. Hence, awareness raising program on child abuse focusing school students is recommended.